Mechanical properties of styrene butadiene rubber toughened graphene reinforced polystyrene - Mohd Shaiful Zaidi, Mat Desa; Suliana, Ab Ghani; M., Yusop; Mohd Bijarimi, Mat Piah; A., Ramli; M. F., Ali (Universiti Malaysia Pahang, 2019)
Polystyrene (PS) is a favorable polymeric material due to its high stiffness and strength as well as good process ability. However, it also possesses a brittleness character, which limits the engineering applications of this material [1]. The modification of polystyrene with addition nanofillers such as graphene nanoplatelets (GNP) results in enhanced condcutivty and strength but is also usually accompanied with a loss in toughness. To overcome this problem there have been several studies aimed at developing toughening methods for polystyrene, such as by using rubber particles as impact modifier [2]. According to Bucknall, (1997) the techniques to toughen polymers are often associated with plastic deformation mechanisms. The development of rubber toughened PS/GNP nanocomposites was a relatively new material concept. To best of our knowledge, there were no attempt made thus far to enhance toughness of PS/GNP nanocomposite by using rubber. Therefore, the objective of this research is to determine the effect of styrene butadiene rubber (SBR) contents on the toughness of PS/GNP nanocomposites. In order to achieve the objectives of the research PS/GNP nanocomposites were prepared with various SBR content styrene butadiene rubber content, while the contents of GNP were fixed at 0.5 wt%.